Spatial distribution and temporal patterns of food tree availability of hornbills (Bucerotidae) at Way Canguk Research Station, Bukit Barisan Selatan National Park, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fitriansyah RA, Setiawan A, Rustiati EL, Utoyo L, Sibarani MC. 2022. Spatial distribution and temporal patterns of food tree availability of hornbills (Bucerotidae) at Way Canguk Research Station, Bukit Barisan Selatan National Park, Indonesia. Biodiversitas 23: 1990-1997. The presence of hornbills in an area is associated with food availability. As more food sources become available, the hornbill population in the area may increase. The purpose of this research was to determine the spatial distribution of hornbill food trees and to determine the long-term temporal fruiting pattern of hornbill food trees at Way Canguk Research Station (WCRS), Bukit Barisan Selatan National Park, Indonesia. We surveyed vegetation plots across the research station to assess the spatial distribution and analyzed long-term phenology survey data of the research station that have been collected from February 1998 to December 2020. We recorded 64 species of hornbill food trees with a total of 911 individuals in 197 of 200 survey plots. The temporal fruiting pattern of hornbill food trees during the last 22 years was relatively stable, with an average of fruiting tree percentage of 10.4% (SD: 3.2%, N: 260 months). The highest percentage of fruiting food trees occurred in September 2008, which amounted to 18.3% and the lowest percentage occurred in September 1998 with a percentage of 2.2%.
Keywords: Ficus spp., food trees, frugivorous animals, hornbill, plant phenology